Educational policies for the inclusion of women in the labor market in exact areas - Silva Dos Santos, Cristina; Laraine Moraes De Assis, Daisy; Maria Radl-Philpp, Rita (Seven Editora, 2023)
In the last decades of the twentieth century, debates about the gender relationship, in general, have been continuously presented in society. When we define the concept of man and woman, some questions range from perceptions about biological sex to concepts constructed predominantly by socio-cultural norms established in consumer societies. We propose to reflect on issues that are directly related to the insertion of women in higher education, as well as the processes of dynamization and popularization of exact sciences as occupational spaces for feminization. We question: what are the causes of the existing educational policy movements propagating for female performance in areas of the exact sciences? What are the educational and social-political relations present in the speeches and actions of entities that promote undergraduate and graduate courses, popularizing the exact sciences for female occupation? To what extent should we consider the feminization of exact sciences courses as a policy for the inclusion of women in places occupied by men? We opted for qualitative research, having as a source the CNPq databases (National Council for Scientific and Technological Development) to identify the participation of men and women in programs offering resources for research fellows in the areas of Exact Sciences, being our main interlocutors Simone de Beauvoir (1980), Alain Touraine (2007) and Louro (2007; 2001). We noticed that the formatting of the sciences was constituted through the binary vision of masculine and feminine, allocating to science values belonging to the masculine pole such as reason, objectivity, and competitiveness of which the feminine is constituted by the opposite. If we were to seek to allocate the characteristics established in the feminine pole, it would be natural to label them as sensitive, emotional beings and, mainly, without abilities for calculation and abstraction. Therefore, with this article, we carried out a brief theoretical and documentary review related to the social constructs of the gender relationship present in undergraduate courses, as well as the presence of women in the areas of knowledge of the exact sciences. Thus, we consider this study fundamental for understanding how society sees the process of including women in the areas of exact sciences in contemporary times, without a reductionist view, but centered on discussions about women. We recognize that the gender relationship is part of the categories present in the reality of social practices, in which we perceive the insertion of discussions about women involving sex-gender-race directed at issues of inequalities in the political, economic, legal, and social spheres. DOI: https://doi.org/10.56238/tfisdwv1-138